Особливості адміністративно-правового статусу біженців і вимушених переселенців - Панова, О. О.; Panova, O. O. (Юридичний бюлетень. – 2021. – Вип. 20. – С. 71-77, 2021)
У статті досліджено особливості адміністративно-правового статусу біженців і вимушених переселенців. Проаналізовано підходи учених-правознавців до розуміння сутності категорії «правовий статус». Установлено, що в більшості випадків сутність правового статусу суб’єкта відповідних суспільних відносин розкривається через перелік його змістових складників, до яких, як правило, віднесено права й обов’язки особи. Обґрунтовано, що такі підходи є доволі вузькими, оскільки поза увагою залишають низку складників правового статусу будь-якої особи. Здійснено аналіз більш широких підходів до розуміння сутності правового статусу особи, завдяки чому з них викреслено зайві для правового статусу біженців і вимушених переселенців змістовні складники. Установлено, що адміністративно-правовий статус біженців і вимушених переселенців об’єктивізовано в нормах адміністративного права. Визначено, що необхідною умовою набуття особою адміністративно-правового статусу біженця або вимушеного переселенця є наявність у неї правосуб’єктності, що розглядається як структурний складник такого статусу. Обґрунтовано, що одним із основних структурних складників адміністративно-правового статусу біженців і вимушених переселенців є їхні права й обов’язки. З’ясовано, що окремим структурним складником адміністративно-правового статусу біженців і вимушених переселенців є міра їх юридичної відповідальності. Визначено, що особливості адміністративно-правового статусу біженців і вимушених переселенців будуть знаходити свій прояв у межах особливостей реалізації окремих із його структурних складників. За допомогою аналізу чинного національного законодавства, на підставі якого здійснюється нормативно-правова регламентація адміністративно-правового статусу біженців і вимушених переселенців, визначено особливості реалізації окремих із його структурних елементів. Надано авторське бачення сутності адміністративно-правового статусу біженців і вимушених переселенців.

The features of the administrative and legal status of refugees and internally displaced persons have been examined in the article. The approaches of legal scholars regarding the understanding of the essence of the category of “legal status” have been analyzed. It has been established that in most cases the essence of the legal status of the subject of the rel- evant social relations is revealed through the list of its substantive components, which, as a rule, include the rights and obligations of a person. It has been substantiated that such approaches are rather narrow, since they ignore a number of components of the legal status of any person. The analysis of broader approaches to understanding the essence of the legal status of an individual has been carried out, due to which the content components, that are irrelevant for the legal status of refugees and forced migrants, have been deleted from them. It has been established that the administrative and legal status of refugees and internally dis- placed persons is objectified in the norms of administrative law. It has been determined that a necessary condition for a person to acquire the administrative and legal status of a refugee or forced migrant is that he or she has quality of being a person in contemplation of the law, which is considered as a structural component of such a status. It has been substantiated that one of the main structural components of the administrative and legal status of refugees and internally displaced persons is their rights and obligations. It has been established that the degree of refugees’ and forced migrants’ legal responsibility is a separate structural com- ponent of their administrative and legal status. It has been determined that the peculiarities of the administrative and legal status of refugees and internally displaced persons will be manifested within the peculiarities of the implementation of its individual structural com- ponents. By analyzing the current national legislation, on the basis of which the legal reg- ulation of the administrative and legal status of refugees and internally displaced persons is carried out, the peculiarities of the implementation of its individual structural elements have been determined. The author's vision of the essence of the administrative and legal status of refugees and internally displaced persons has been provided.

В статье исследованы особенности административно-правового статуса беженцев и вынужденных переселенцев.
Special aspects of the administrative and legal status of refugees and internally displaced persons
Панова, О. О. Особливості адміністративно-правового статусу біженців і вимушених переселенців / Панова Оксана Олександрівна // Юридичний бюлетень. – 2021. – Вип. 20. – С. 71-77. – DOI: https://doi.org/10.32850/LB2414-4207.2021.20.10
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; біженці; вимушені переселенці; правовий статус; беженцы; вынужденные переселенцы; правовой статус; refugees; internally displaced persons; legal status